Review of Performance Analysis of Lithium-Sulfur Batteries for Electric Vehicles: Challenges and Future Prospects - Akri, Akri; Lidong, Andini (Indonesian Journal of Green Chemistry, 2024)
The automotive sector has witnessed rapid technological advancements, particularly in developing electric vehicles (EVs), which rely heavily on batteries for energy supply. While lithium-ion batteries are the predominant choice, they face significant challenges, including low energy density and usage limitations. As a result, researchers are exploring alternative battery technologies such as lithium-air, lithium-sulfur, and all-solid-state batteries to potentially replace conventional lithium-ion batteries in electric vehicles. This review aims to compare the performance of these alternative battery types, focusing specifically on lithium-sulfur (Li-S) batteries, which have demonstrated an energy density of 2,500 Wh/kg. This surpasses the energy densities of lithium-air batteries (250-1200 Wh/kg), all-solid-state batteries (500 Wh/kg), and lithium-ion batteries (890 Wh/kg), highlighting their significance in energy storage capacity. Given their impressive energy density and increasing attention, Li-S batteries are rapidly advancing toward mass commercialization than their lithium-ion and all-solid-state counterparts. However, several challenges remain to be addressed, particularly in enhancing battery development to ensure timely integration into the market.